Analysis of emission and combustion behaviors of water-emulsified diesel with various water contents and droplet diameters - Ghazian Amin Bin MUKHTAR; Takeshi NAGATA; Jun HAYASHI; Naoto HORIBE; Hiroshi KAWANABE; Manabu FUCHIHATA (Journal of Thermal Science and Technology)
This study investigates the combustion and emission characteristics of water-in-diesel emulsified fuels, focusing on varying water content and droplet sizes. Emulsified fuels were prepared with water contents ranging from 2 to 24 vol% and droplet diameters of <3 μm, 26.5 μm, and 39.8 μm, produced using both strong stirring and membrane emulsification methods. These fuels were tested in a single cylinder, air-cooled direct injection diesel engine at a constant speed of 2300 rpm. The results showed that increasing water content generally decreased engine output power due to reduced diesel fraction and latent heat effects. However, thermal efficiency improved up to 14 vol% for small droplets and 20 vol% for larger droplets, driven by an extended ignition delay and higher peak heat release during premixed combustion. Beyond these water content thresholds, thermal efficiency declined due to increased ratio of phase-specific combustion durations after and before CA50 i.e., burn ratio, leading to energy losses from prolonged diffusion-controlled combustion. Emission measurements indicated that higher water content reduced NOx and soot emissions but increased CO levels. This study concludes that emulsified fuels with larger water droplets and 20 vol% water content offer the best balance between thermal efficiency and emission reduction.